Questions of inheritance: Erasmus and Charles Darwin - Fara, Patricia (Romanticism and Victorianism on the Net, 2016)
Would Charles Darwin have developed the concept of natural selection if he had been born into a different family? Although Darwinian natural selection is situated within the context of Victorian capitalism, there is also clear evidence that Charles studied the evolutionary ideas of his grandfather, Erasmus Darwin. In this essay, I examine the evidence testifying to connections between them. Familial and broader contextual effects are inevitably intertwined, but I divide influences into two major strands: those passed down directly through family interactions, and those more closely tied to particular books. Charles’s family history inclined him towards thinking about inheritance, and while it is impossible to pin down a causal relationship for the similarities in their religious views, it does seem certain that Charles acquired his abhorrence of slavery from his family. Annotations confirm that Charles read his grandfather’s books closely, notably Zoonomia (1794-6) and The Temple of Nature (1803). Both Darwins shocked their critics by denying divine direction, yet by presenting evolution through natural selection as the only viable alternative to repeated miraculous creation, Charles effectively concealed his grandfather’s suggestion that life had stemmed from a single event of spontaneous generation. Death, argued Erasmus, is essential for preventing a population explosion that would outrun the world’s resources, a Malthusian concept that was crucial for Charles’s development of natural selection. The extent of Erasmus Darwin’s influence on his grandson must remain speculative, but it cannot be dismissed.